Budaya Organisasi dan Perannya dalam Mempertahankan Eksistensi Sekolah PAUD - Anwar, Saiful; Utaminingsih, Sri; Nurlaili, Lili; C. Bien, Jonna Karla; Said Permana, Putut (Universitas Pamulang, 2024)
Organizational culture is a value shared by an organization. Apart from being able to increase teacher professional commitment, in theory organizational culture is believed to be able to improve teacher performance. Organizational culture can also be said to be a set of value systems, beliefs or assumptions that are valid and agreed upon and carried out by all members of the organization as a guide to behavior, speech and action. Having a strong and good organizational culture will of course make the organization's direction towards organizational goals easier, apart from that, a strong and good organizational culture will also form bonds or relationships between members which will ultimately improve performance together. However, organizational culture can change and weaken depending on how the leader implements it. Often a change of leader will cause the organizational culture to shift according to the style and leadership style of a school principal. This PKM is present at PAUD (early childhood education programs) Mawar Biru in order to provide reinforcement to teachers at PAUD Mawar Biru about the importance of an organizational culture in schools and how to ensure that the existing organizational culture is able to improve the performance of PAUD teachers themselves. Keywords: Organizational Culture, early childhood education programs, Teachers